2013
DOI: 10.1177/1362361312470495
|View full text |Cite
|
Sign up to set email alerts
|

Adapted shared reading at school for minimally verbal students with autism

Abstract: All four students showed increased story comprehension and engagement during adapted shared reading. Average percentage of session engaged was 87%-100% during adapted sessions, compared with 41%-52% during baseline. Average number of correct responses to story comprehension questions was 4.2-4.8 out of 6 during adapted sessions compared with 1.2-2 during baseline. Visual supports, tactile objects, and specific teaching strategies offer ways for minimally verbal students to meaningfully participate in literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 26 publications
1
60
1
2
Order By: Relevance
“…The development of literacy skills is one of the foremost aims of education, not only as a life skill but also because it provides access to all other curriculum areas (DfE, ). Mucchetti () advocates the creation of ‘effective curricula, including literacy interventions, for students with autism’. However, when developing a curriculum for any student, it would make sense to have a way to measure its effectiveness, and the assessment of individual ability, and tracking progress, fulfils that role.…”
Section: Discussionmentioning
confidence: 99%
“…The development of literacy skills is one of the foremost aims of education, not only as a life skill but also because it provides access to all other curriculum areas (DfE, ). Mucchetti () advocates the creation of ‘effective curricula, including literacy interventions, for students with autism’. However, when developing a curriculum for any student, it would make sense to have a way to measure its effectiveness, and the assessment of individual ability, and tracking progress, fulfils that role.…”
Section: Discussionmentioning
confidence: 99%
“…The second found that 1:1 sessions increased the rate of verbalization, number of communicative exchanges, and length of book reading session among preschool children with ASD as compared to baseline conditions (Fleury, Herriott Miramontez, Hudson, & Schwartz, 2014). The third included visual supports and focused on children with ASD who used little language, who were found to improve their responsiveness and engagement (Mucchetti, 2013). The fourth study was conducted with pairs of children with ASD and found that all four participating children had fewer incorrect responses and more frequent correct, spontaneous responses in comparison to baseline (Whalon, Martinez, Shannon, Butcher, & Hanline, 2015).…”
Section: Emergent Literacy Interventionsmentioning
confidence: 99%
“…An important activity in emergent literacy interventions is shared reading, where an adult reads aloud to children (Lennox, ). The adult uses shared reading to enhance question asking and discussion, thus providing a framework for advancing language and literacy skills during the joint literary interaction (Mucchetti, ). Joint reading can include various activities that promote book concepts (e.g., book cover, title, author, illustrator, pages) and print concepts (e.g., distinction between pictures and print; writing direction: left‐to‐right or right‐to‐left).…”
mentioning
confidence: 99%
“…Hudson and Test () reviewed the literature regarding the use of shared story reading to promote the literacy of students with extensive support needs (including students with ASD), and found a moderate level of evidence supporting the use of this strategy to promote literacy. Since then, intervention studies (Mucchetti, ; Whalon, Shannon, Martinez, et al., ) that specifically targeted shared reading for children with ASD showed that these children can indeed benefit from such interventions, especially when directed towards language comprehension, communication and participation. Shared reading enables children with disabilities to enjoy and learn from texts that they cannot read independently and also increases opportunities for communication and literacy development (Mims, Browder, Baker, et al., ).…”
mentioning
confidence: 99%